Functional traits above and below ground allow species with distinct ecological strategies to coexist in the largest seasonally dry tropical forest in the Americas - Fagundes, Marina Vergara; Souza, Alexandre F.; Oliveira, Rafael S.; Ganade, Gislene (Frontiers in Forests and Global Change, 2022)
Plant functional strategies are well established for low- and high-stress environments such as rainforests and deserts. However, in environments with low- and high-stress level fluctuation within years, the relationship between plant functional strategies and their spatial distribution is still poorly understood. We aimed to answer: what are the relationships between above- and below-ground traits in the largest seasonally dry tropical forest in the Americas? Do the studied species form detectable groups from the functional perspective? If detectable, do functional groups present distinct spatial distributions across the domain, mediated by spatial heterogeneity of aridity. We sampled a range of 16 above and below-ground traits from the 20 most common native tree species. We performed a PCA to understand species main coordinated trade-offs, a k-mean analysis to test for functional groups and Ripley's-K analysis followed by a GLS model to test spatial functional groups distribution through the aridity gradient. We found five coordinated trade-offs representing different aspects of the conservative-acquisitive strategy continuum. Drought-tolerance and avoidance mechanisms seem linked to the conservative-acquisitive gradient, where water storage positively correlated with acquisitive strategies. Different from other seasonally dry regions, acquisitive strategies are not limited by aridity. The presence of short-term water storage traits might buffer rainfall fluctuations, allowing acquisitive species to occupy more arid regions. This study sheds new light on the functional complexity of species from Americans seasonally dry tropical forests, for the first time including the relationship of its below- and above-ground traits.